Effects of body mass index in pregnant women on fundal height charts - Anar Kystaubayeva; Gulyash Tanysheva; Yuliya Semenova; Ion Bologan; Zhanar Kaliyeva; Meruert Sharipova (National Scientific Medical Center, 2017)
Aim: To evaluate the eﬀects of body mass index on fundal height charts. Methods: Design: Cross-sectional study. The study complies with the principles of the Helsinki Declaration. Approved by the Ethics Committee of The Semey State Medical University protocol No.2 of 14.11.2014. Study was conducted in Semey and in the region within January-December, 2014. We identifed 2387 cases of uncomplicated pregnancy ended in childbirth of full-term fetus in cephalic presentation, with a weight between 2,500 and 4,000 grams. Depending on the body mass index, the cases were divided into 3 groups. The frst group included pregnant women with a body mass index of less than 18.5. The second group included cases with body mass index of 18.5-24.9 while the third group included pregnant women with an index greater than 24, which corresponds to overweight and obesity. Statistical analysis was performed with SPSS package, version 20. We used descriptive statistics and nonparametric tests for unpaired samples (Kruskal Wallis and Mann-Whitney). Results: Statistically signifcant diﬀerences were identifed between the average fundal height indexes in all stages of gestation (p = 0.001), except for 22 weeks (p = 0347) and 28 weeks (p = 0.14). Pairwise comparisons with MannWhitney test between "defcit weight - normal weight" and "defcit weight - overweight, obesity" and "normal weight - overweight, obesity" groups showed no statistically signifcant diﬀerence in fundal height of pregnant women with underweight and normal weight at pregnancy terms of 24, 25, 34, and 35 weeks. At 26 and 31 weeks of pregnancy there were no statistically signifcant diﬀerence in pregnant women with normal weight and overweight. In other cases, the diﬀerences between study groups in fundal height were statistically signifcant. Conclusions: Body mass index is a variable that aﬀects the character of fundal height curve. To enable high-quality antenatal carem we need to use the curves tailored to anthropometric indicators.